Design of NLP-based chatbot media as a mental health consultation media with Depression Anxiety Stress approach - Hadi, Abd (Internet of Things and Artificial Intelligence Journal, 2025)
The development of technology has increased rapidly, this is in line with the increasing consumption of data and information. Getting information for all users has become easier with the development of artificial intelligence, Chatbot is partly an example of artificial intelligence technology that allows machines to think and make decisions independently, Depression Anxiety Stress Scales (DASS) is a commonly used tool for measuring mental health conditions, consisting of a series of questions used to measure a person's level of depression, anxiety, and stress. DASS helps provide a better picture of a person's psychological condition, which can help further diagnosis and intervention. In this study, we conducted a chatbot design using the NLP approach using DASS data as many as 3 categories of anxiety, stress, and depression. From the test results obtained by the chatbot from 41 questions, there were 85% percent accurate answers.